Systematic Review of Patient-Reported Outcome Measures for Patients with Exercise-Induced Leg Pain - Castillo-Domínguez, Alejandro; García-Romero, Jerónimo; Alvero-Cruz, José Ramón; Ponce-García, Tomás; Benítez-Porres, Javier; Páez-Moguer, Joaquín (IOAP-MPDI, 2022)
Background and Objectives: To determine the most commonly used patient-reported outcome measures (PROMs) in exercise-induced leg pain (EILP) and to identify specific PROMs for EILP in order to evaluate their psychometric properties and methodological quality. Materials and Methods: A strategic search was performed in different databases to identify and extract the characteristics of studies based on the use of PROMs in patients with EILP. Specific PROMs were evaluated according to the Terwee et al. and COSMIN criteria. Results: Fifty-six studies were included in the review. The Medial Tibial Stress Syndrome Score (MTSSS), Lower Extremity Functional Scale (LEFS) and Exercise-Induced Leg Pain Questionnaire (EILP-Q) were identified as specific PROMs for EILP. The Visual Analog Scale (VAS) was the most widely used instrument in the assessment of EILP. The methodological quality assessment showed six positive values for the LEFS, four for the MTSSS and three for the EILP-Q for the eight psychometric properties analyzed according to the COSMIN criteria. The evaluation of the nine psychometric properties according to Terwee showed five positive values for the LEFS and MTSSS, and three for the EILP-Q. Conclusions: The overall methodological quality of the PROMs used was low. The VAS was the most widely used instrument in the assessment of EILP, and the LEFS was the highest quality PROM available for EILP, followed by the MTSSS and EILP-Q, respectively.
Keywords: Psicometría; Exercise-induced leg pain; Medial tibial stress syndrome; Chronic exertional compartment syndrome; Stress fracture; Running; Psychometrics; Patient-reported outcome measures